Analisis Implementasi Sistem Manajemen Mutu ISO 9001:2008 Pada Sekolah Tinggi Ilmu Administrasi Mandala Indonesia - Dony Hendartho (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2014)
Implementation of Total Quality Management makes organization to maintain quality standards in all aspects of organization's business. Standard quality management system (QMS) that has been developed and suitable for education is ISO 9001, achievement of quality device that is expected to respond to the challenges of globalization by increasing the efficiency and effectiveness to satisfy stakeholders. Higher School of Administration Sciences of Mandala Indonesia (STIAMI) proved itself as a reliable organization that received the ISO 9001:2008 certificate issued by QS Zurich AG no. 7011 on April 19, 2011.This research aims are (1) To determine the implementation of Quality Managements System ISO 9001:2008 from the aspect of dokumentation, (2) To determine the implementation of Quality Managements System ISO 9001:2008 from the aspect of management responsibility and alternative implementation strategies for corrective action.The data used in the form of primary and secondary data, both from qualitative and quantitative. Processing of qualitative data using descriptive analysis is based on interviews with party organization consists of nine informen who master the Quality Management System and its implementation in STIAMI on the right target and can affect policy. The collected data is processed by the method of analytic hierarchy process AHP with Microsoft Excel 2010 software, version AHPcalc 12:08:13.The results of data processing show that the essential elements of QMS ISO 9001:2008 in STIAMI are Quality Management System (25.8 %), Responsibility Management (25 %), Product Realization (23.8%), Measurement, Analysis & Improvement (17 , 4 %) and Resource Management (8%); the most responsible actor is Top Management (51.4 %); goals to be achieved are the Quality Improvement Services (59.7 %), Improvement of Administration (31.2 %) and Reference (9.1 %); alternative measures such as Education and Training (1st priority), Monitoring and Evaluation (2nd priority) and Teamwork (3rd priority)          Based on this research, it can be concluded that the implementation of QMS ISO 9001:2008 in STIAMI is going well.